Tertiary treatment of palm oil mill effluent (POME) by the combination of microalgae and activated sludge using sequential batch reactor - Chua, Gek Kee; Chin, Sim Yee; Zainol, Norazwina (2016)
Microalgae was found to have potential to reduce biochemical oxygen demand (BOD) level and colour of black-coloured wastewater like Palm Oil Mill Effluent (POME) in palm oil industry. The major factor that will influent the effectiveness of microalgae in tertiary treatment of POME was light penetration. This project presents the effect of light penetration and kinetic study in tertiary treatment of Palm Oil Mill Effluent (POME) by utilizing microalgae. An alternative option of using activated sludge system was also examined. 10% v/v of microalgae was cultured in serially diluted (10 % to 100 % v/v), autoclaved and centrifuged POME. Sampling was done at the beginning and the end of seven days to observe the microalgae growth under light irradiance of 6000 Lux. Kinetic study was then carried out on the sample with the highest growth rate to observe growth profile of microalgae mix culture within seven days at interval of 24 hours. The BOD and colour of initial sample (autoclaved and centrifuged POME without microalgae) and final sample (at t = 7 days) was determined by applying dilution method (Standard Method 5210B) and ADMI weighted ordinate method respectively. Results revealed that microalgae experienced the highest growth rate at 30 % v/v POME. The minimum light penetration was approximately 2000 Lux corresponding to the light penetrated in 30 %v/v of POME. The microalgae cultured in 30 % v/v of POME had the highest specific growth rate (1.39 d-1) and biomass productivity (0.61 g/L.d). The ratio of POME concentration and the respective growth profile of microalgae led to the similar removal efficiency of BOD. While the low decolourisation yield (colour removal efficiency less than 20%) proved that microalgae was not effective in removing coloured compound. In a separate study, the effect of initial pH of POME (4 -10), hydraulic retention time (12 – 72 h), organic loading rate (200 – 1000 mg/L), mixed liquor suspended solids (1000 – 10000 mg/L), solid retention time (2 – 20 days) and addition of molasses as external carbon source (10 – 100 mg/L) into the activated sludge treatment system using sequential batch reactor and microorganism from palm oil refinery were investigated. Initial pH at 6.5, hydraulic retention time of 48 h, solid retention time of 10 days, initial MLVSS value at 2000 mg/L and organic loading rate of 650 mg/L, together with the feeding of 60 mg/L of molasses at the beginning of treatment, enable a BOD reduction of up to 65%. The new discharge requirement, however, could not be met. In short, it is possible that the non-degradable or slow-degradable organic compounds existed in the POME hinder the complete treatment of the waste.